STRENGTHENING HIGH SCHOOL STUDENTS' DIGITAL CITIZENSHIP THROUGH SOCIAL MEDIA-BASED CIVICS EDUCATION - Agung Tesa Gumilar; Ade Suherman; Hilmy Nurfaizan AM (Journal Civics And Social Studies, 2026)
The advancement of digital technology requires senior high school (SMA) students to possess adequate digital citizenship, yet Civic Education (PPKn) instruction in schools remains dominated by conventional methods that are less relevant to students as digital natives. This study aims to determine the effect of social media-based PPKn learning on strengthening the digital citizenship of students at SMA Pramita Tangerang. The study employed a quantitative method with a quasi-experimental nonequivalent control group design, involving 32 students in the experimental class and 30 students in the control class. Data were collected through a digital citizenship questionnaire based on Ribble's nine elements, administered as a pretest and posttest, then analyzed using normalized N-Gain and simple linear regression with the aid of SPSS version 27. The results show that the experimental class, which received social media-based PPKn learning, achieved a High N-Gain category (0.76), significantly higher than the control class, which only reached the Moderate category (0.41). The simple linear regression results show an R Square of 0.581 with F = 83.204 and a significance of .000 (p < .05), indicating that social media-based PPKn learning has a significant and large effect on strengthening students' digital citizenship. This study recommends the structured integration of educational social media into PPKn learning in senior high schools to strengthen students' digital citizenship.